Proceedings of SAE-China Congress 2014: Selected Papers - Zhongguo qi che gong cheng xue hui (Springer, 2015)
These Proceedings gather outstanding papers submitted to the 2014 SAE-China Congress, the majority of which are from China, the most dynamic car market in the world. The book covers a wide range of automotive topics, presenting the latest technical achievements in the industry. Many of the approaches it presents can help technicians to solve the practical problems that most affect their daily work.